Relationship Between Body Composition Characteristics and Physical Performance in Male Karate Athletes: An Observational Study - Herrera-Valenzuela, T (ASOC ESPANOLA DIETISTAS NUTRICIONISTAS, 2020)
Introduction: The purpose of this study was to examine the relationship between body composition characteristics and components of physical performance in male karate athletes from Chile. Material and Methods: Observational design with 18 male athletes competing in different age categories in regional and national competitions. Body Mass (MC), Fat Mass (MG), % Fat Mass (%MG), Muscle Mass (MM), Squat Jump (SJ), Countermovement Jump (CMJ), linear speed at 0-5 meters, Change of Direction (COD) and the 20 Meters Shuttle Run (20MSR) test were evaluated. Results: The sample was made up of 18 athletes with the following characteristics: 16.4 (3.5) years; 167.3 (7.3) cm; 69.5 (11.8) kg; 3 (1) years of experience regularly. Among the main findings of this study in terms of average, an increase in MC and MM was documented as age advances. MG fluctuated and a lower MG and %MG were documented in the 6-17 years category. In terms of the physical performance (RF) in SJ, CMJ, COD, superior performance was observed in the 16-17 years category. Furthermore, significant relationships (p<0.05) were documented between MG and SJ (r=-0.49), CMJ (r=-0.55) and 10-M (r=0.53). So also between %MG and SJ (r=-0.61), CMJ (r=-0.64). As moderate to low relationships were documented between the MM and the variables analyzed. Conclusions: The data from the present study show that fat mass and % fat mass will be related more than muscle mass and body mass with physical performance in youth karate athletes. Coaches may consider strategies to decrease fat mass and maintain muscle mass to optimize performance in karate athletes.